Nurses’ Role in Home Care for Older People with Sarcopenia - Tongma, Sichon; Klinpudtan, Nonglak; Sawangchit, Siriporn; Bandansin, Jutarat; Srithumsuk, Werayuth (Journal of The Royal Thai Army Nurses, 2021)
Sarcopenia is one of the frequently-found geriatric syndromes. In Thailand, sarcopenia prevalence was 1 in 3 in the general population by 32.5 percent in males and 34.5 percent in females. Sarcopenia increased more in advanced age. Sarcopenia was caused by increasing illness, risk of frailty, limited activity daily living, increased risk of falls and cardiovascular diseases, decreased workability and quality of life, and increased treatment and mortality cost. Therefore, community and home healthcare nurses who work closely with older people at home had the role for assessment and screening the risk group of sarcopenia and assessment of complication after sarcopenia especially fall, promoting physical activity and exercise both resistance and aerobic exercises, promoting nutritional status, and withdrawing/quitting smoking and drinking which were important to promote the function of physical in older people. These will let the older people live independently, with no burden to the family and caregivers. It was also the quality indicators of community and home healthcare nurses in taking care of older people.